Laboratory safety guideline - Hanum, Hassan; Azuddin, Bahari; Faridah, Wahab (Universiti Malaysia Perlis, 2009)
Laboratory workplace must be safe and conducive for all workers to work. Workers in chemical laboratories or are designated as Chemical Technologist and Technicians are exposed to lots of hazards. In some the hazards are well recognized. Where hazards are recognized, precautionary measures can be taken. Thus, all workers need to be aware of the issues that have an effect on their health and safety at the workplace. Accidents at the workplace happen due to various reasons i.e. from laboratory facilities to nature of work. Consequently in order to ensure a safety, healthy and a favorable working environment, proper safety procedures at the workplace must devise and adhere to. At this juncture, both the employer and employees ought to be well-informed of some of the laws which have bearing on laboratory safety such as the “Occupational Safety and Health (Use and Standards of Exposure of Chemicals Hazardous to Health) Regulations 2000, Occupational Safety and Health (Classification, Packaging and Labeling of Hazardous Chemicals) Regulation 1997 and Environmental Quality Act, 1974 vis-à-vis the Environmental Quality (Scheduled Wastes) (Amendment) Regulations 2007”. This paper aim to inform the employers and the laboratory worker on the relevant laws and the safety practices which is common to all laboratory operators. It is hope that this guideline should help to avoid accidents at the workplace.